PENGUKURAN KINERJA PERUSAHAAN DAN SISTEM MANAJEMEN STRATEGIS - Yoyon Safrianto (universitas teuku umar, 2017)
Abstract Nowadays, the companies are in the middle of the information competition century. To achieve competitive success, the century information environment requires the new ability of the companies must be owned by the manufacturing and services. A company's ability to process information from a variety of instruments is absolutely need, steer the company to across the complex competitive environment. Company requires instrument which capable of explaining various aspects of the environment and performance in monitoring of travel towards a promising future. Balanced Scorecard provides an instrument that is required to steer the company toward the future success of the competition. An accurate understanding about the goals and methods for achieving it is very vital. Balanced Scorecard translates mission and strategy of the company in to a comprehensive measure that provides a framework for measurement and strategic management system. Scorecard measures the performance of companies on the four perspectives of balanced: financial, customer. internal business processes, and learning growth. Balanced Scorecard enables companies to record financial performance results as well as monitor progress in building the company's ability and to obtain intangible assets that required for future growth. Keywords: balanced scorecard, performance, and trategic management system